Pengembangan Media Genially pada Materi Volume Kubus Dan Balok di Sekolah Dasar - Anwar, Muhfik; Murtiyasa, Budi; Hidayati, Yulia Maftuhah; Minsih, Minsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to, (1) Develop the Genially learning media on the topic of volume for cuboid and rectangular prism in elementary schools, and (2) Assess the feasibility level of the Genially learning media named "Volkuba" in the subject of mathematics. The research method used is Research and Development (R&D) with the ADDIE model, which aims to develop and produce a product. This study is limited to the validation testing phase, with data collection techniques using observation and validation sheets from media and content experts. The validation results show that this media has a high feasibility percentage, namely 81.6% for content experts and 94.4% for media experts. Based on these results, the Genially "Volkuba" media is highly feasible to be used as a learning tool for volume topics in elementary school mathematics. Based on pretest and posttest data, this media has proven to be effective in improving students' understanding. The experimental group that used this media showed significant improvement, with some students reaching the maximum posttest score, while the control group showed smaller improvement. The interactive features and 3D visualization in Genially allow students to better understand the concepts of spatial shapes. This media also provides immediate feedback through quizzes and exercises, helping students quickly improve their understanding. Overall, the Genially "Volkuba" media has proven to be effective and suitable for use in mathematics learning.